Location Analysis of Freight Distribution Terminal of Jakarta City, Indonesia - Nahry Nahry; Tri Tjahjono; Bima Iriantika; Jarot Mulyo Semedi (Institute of Research and Community Outreach - Petra Christian University, 2016)
Currently Jakarta has two freight terminals, namely Pulo Gebang and Tanah Merdeka. But, both terminals are just functioned for parking and have not been utilized properly yet, e.g. for consolidation. Goods consolidation, which is usually performed in distribution terminal, may reduce number of freight flow within the city. This paper is aimed to determine the best location of distribution terminal in Jakarta among those two terminals and two additional alternative sites, namely Lodan and Rawa Buaya. It is initialized by the identification of important factors that affect the location selection. It is carried out by Likert analysis through the questionnaires distributed to logistics firms. The best location is determined by applying Overlay Analysis using ArcGIS 9.2. Four grid maps are produced to represent the accessibility, cost, time, and environment factors as the important factors of location. The result shows that the ranking from the best is; Lodan, Tanah Merdeka, Pulo Gebang, and Rawa Buaya.